Sosialisasi Peningkatan Kualitas dan Pemasaran Produk Batako sebagai Solusi Pembangunan Berkelanjutan Dusun Dasan Baru Desa Sukarara - Syahida, Nidya Putri; Yusuf, Siti Yulianah M; Iswan, Iswan; Nasruddin, Nasruddin (Pakis Journal Institute, 2025)
Concrete block products are among the most widely used building materials in infrastructure development, both in urban and rural settings. However, the quality of concrete blocks produced by small-scale rural enterprises often does not meet established standards and is further constrained by limited marketing strategies. This community service program aims to improve the knowledge and skills of concrete block producers in the partner village through outreach, training, and mentoring focused on product quality improvement and marketing enhancement. The methods implemented include problem identification, educational sessions, hands-on training on standardized concrete block production, and digital-based marketing workshops. The results demonstrate an increase in participants’ knowledge, improved product quality characterized by denser and more uniform concrete blocks, and the development of more diverse marketing strategies. This program contributes to sustainable development by strengthening the local economy and creating employment opportunities.